2019
DOI: 10.3390/microorganisms7110512
|View full text |Cite
|
Sign up to set email alerts
|

Red-Brown Pigmentation of Acidipropionibacterium jensenii Is Tied to Haemolytic Activity and cyl-Like Gene Cluster

Abstract: The novel Acidipropionibacterium genus encompasses species of industrial importance but also those associated with food spoilage. In particular, Acidipropionibacterium acidipropionici, Acidipropionibacterium thoenii, and Acidipropionibacterium jensenii play an important role in food fermentation, as biopreservatives, or as potential probiotics. Notably, A. jensenii and A. thoenii can cause brown spot defects in Swiss-type cheeses, which have been tied to the rhamnolipid pigment granadaene. In the pathogenic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The latter is supported by the hemolytic and cytolytic activity of the Granadaene pigment in GBS (Whidbey et al, 2013(Whidbey et al, , 2015bBoldenow et al, 2016) and cyl-expressing L. lactis (Figures 1, 2). The presence of an identical or similar hemolytic pigment in a range of Gram-positive bacteria with cyl genes (Vanberg et al, 2007;Deptula et al, 2019), as well as our heterologous expression experiments, suggest that Granadaene can potentially function across a physiologically diverse group of organisms if they likely possess a Gram-positive-type cell wall structure. In fact, a recent study correlated pigmentation with hemolysis and cyl gene expression in Acidipropionibacterium species that have roles in cheese production and food preservation (Deptula et al, 2019).…”
Section: The Evolution Of Cyle and Cylf Conferred Critical Functions mentioning
confidence: 69%
See 1 more Smart Citation
“…The latter is supported by the hemolytic and cytolytic activity of the Granadaene pigment in GBS (Whidbey et al, 2013(Whidbey et al, , 2015bBoldenow et al, 2016) and cyl-expressing L. lactis (Figures 1, 2). The presence of an identical or similar hemolytic pigment in a range of Gram-positive bacteria with cyl genes (Vanberg et al, 2007;Deptula et al, 2019), as well as our heterologous expression experiments, suggest that Granadaene can potentially function across a physiologically diverse group of organisms if they likely possess a Gram-positive-type cell wall structure. In fact, a recent study correlated pigmentation with hemolysis and cyl gene expression in Acidipropionibacterium species that have roles in cheese production and food preservation (Deptula et al, 2019).…”
Section: The Evolution Of Cyle and Cylf Conferred Critical Functions mentioning
confidence: 69%
“…The presence of an identical or similar hemolytic pigment in a range of Gram-positive bacteria with cyl genes (Vanberg et al, 2007;Deptula et al, 2019), as well as our heterologous expression experiments, suggest that Granadaene can potentially function across a physiologically diverse group of organisms if they likely possess a Gram-positive-type cell wall structure. In fact, a recent study correlated pigmentation with hemolysis and cyl gene expression in Acidipropionibacterium species that have roles in cheese production and food preservation (Deptula et al, 2019). Accordingly, the hemolytic and cytotoxic properties of other pigmented, cyl operon-containing microbes found in soil environments or utilized for industrial application warrant further examination.…”
Section: The Evolution Of Cyle and Cylf Conferred Critical Functions mentioning
confidence: 69%
“…One methylation motif was detected for each of the strains. Annotation with the NCBI Prokaryotic Genome Annotation Pipeline (PGAP) ( 7 ) and SEQWARE methylome analysis at REBASE ( 8 ) were performed as previously described ( 9 ).…”
Section: Announcementmentioning
confidence: 99%
“…c May turn orange to pink if kept for 3 weeks. d Corresponding to granadaene production according to Deptula et al (2019).…”
Section: Metabolismmentioning
confidence: 99%
“…Piveteau et al (2000) suggested that the presence of immunoglobulins, transferrin, lactoferrin, lactoferrin-derived, or casein-derived proteins might cause inhibition of PAB. Controversially, Deptula et al (2019) observed that pigmented strains of A. thoenii and A. jensenii are somehow protected against growth inhibition caused by whey filtrates.…”
Section: Dairy Pab In Cheese Productionmentioning
confidence: 99%